Síntese de cicloexanonas quirais utilizando organocatálise - Oliveira, Igor Holanda [UNIFESP] (2017)
The organocatalysis is a methodology that makes use of organic molecules of low molar mass to catalyze organic reactions. This strategy has been widely employed in organic synthesis and has provided the preparation of a wide variety of structurally complex chiral organic compounds in an diastereoselective and enantioselective manner. This methodology has experienced exponential growth since 2000, as it allows the use of various organic molecules as organocatalysts in promoting various organic reactions. The constant preoccupation with the environment has provided an enormous gain in the area of synthetic organic chemistry in the sense that several research groups have concentrated their efforts in the development of new methodologies that provide the preparation of organic compounds with a considerable reduction of residues generated in the process. In this sense, cascade reactions, especially Michael/Aldol type, have received a prominent role in the preparation of new compounds, since it is possible to perform two or more reactions in a single operation, without the need for addition of any other reagents thereby decreasing the volume of solvents spent in purification processes. In this work, several reactive studies were carried out in the promotion of the Michael/Aldol cascade reactions by the use of primary and secondary amines. The best results were achieved by utilization dipeptide di-L-phenylalanine in 20 mol% in NMP solvent. In this study the best conversion rate was of 52% and 79% ee were achieved. The application of primary amines as organocatalysts in cascade reactions of the Michael / Aldol type has proved quite promising. Further studies should be carried out to optimize the reaction conditions and also seek the discovery of other compounds that provide the formation of the Michael / Aldol product in high yields and stereoselectivity.